Investigating the influence of corporate governance on listed companies performance: evidence from the palestine stock exchange - Abueid, Raed; Adam, Ibrahim Muhammad; Galadima, Mukhtar Danladi (Journal of Management and Science, 2021)
The purpose of this studyis to determine the relationship between corporate governance and return on equity (ROE);to examine the relationship between corporate governance and return on assets (ROA); and to analyze the relationship between corporate governance and earnings per share (EPS). To achieve the objective of the study, Fixed and Random Effect Models were employed to analyze the data.The findings revealed a negligible relationship between corporate governance and firm performance. However, when the study is controlled for financial leverage and total assets, a significant relationship between corporate governance and firm performance has been found.The practical implication of the results is that listed firms in Palestine should pay significant attention on enhancing the application of CG principles, uphold and ensure the board’s commitment to its responsibilities, and ensure that adequate disclosure procedures are in place including the evaluation mechanism used for assessing the performance of the board.Based on the findings, the study recommends that listed firms in Palestine should pay significant attention on enhancing the application of CG principles so as to better protect shareholder rights; uphold and ensure the board’s commitment to its responsibilities; and ensure that adequate disclosure procedures are in place including the evaluation mechanism used for assessing the performance of the board, its committees, and individual directors. Likewise, improving good CG practice should offer investor safety, reduce risk investment and sustain positive relationships between the company and its stakeholders which could result in higher growth in stock costs. It also recommends to the Palestinian Capital Market Authority (PCMA) to issue a stricter enforcement of CG legislation with special measures to be taken against those evading them.